Closing the Global Marine 226Ra Budget Reveals the Biological Pump as a Dominant Removal Flux in the Upper Ocean - Bochao Xu; M. Bayani Cardenas; Isaac R. Santos; William C. Burnett; Matthew A. Charette; Valentí Rodellas; Sanzhong Li; Ergang Lian; Zhigang Yu (Geophysical Research Letters)
Abstract Radium isotopes are powerful proxies in oceanography and hydrology. Radium mass balance models, including assessments of submarine groundwater discharge (SGD), often overlook particle scavenging (PS) as a pathway for dissolved radium removal from the world ocean. Here, we build a global ocean 226Ra mass balance model and reevaluate the potential importance of PS. We find that PS is the major 226Ra sink for the upper ocean, removing about 96% of the total input from various sources. Aside from vertical exchange with the lower ocean, SGD is the largest 226Ra source into the upper ocean. The biological pump transfers particles to the deep ocean, resulting in a major but often overlooked impact on the global 226Ra marine budget. Our findings suggest that radium mass balance models should consider PS in systems with high siliceous algae production and export fluxes and long water residence times to prevent underestimation of large‐scale SGD fluxes.